Study on Flexural Properties of Basalt Fiber Textile Reinforced Concrete (BTRC) Sheets Including Short AR-Glass Fibers - Zhang, Qin; Li, Sanya; Gong, Susu; Zhang, Guanhua; Xi, Guangheng; Wu, Yaoqing (Frontiers in Materials, 2020)
Experimental investigations were carried out to determine the mechanical properties of fine-grained concrete with short AR-glass fibers including the effects of fiber content and length. The basalt fiber textile reinforced concrete (BTRC) sheets with short AR-glass fibers were tested under four-point bending, and the effects of the number of textile layers and fiber length on the flexural properties were analyzed. The results show that the mechanical properties of fine-grained concrete with fibers were mainly related to fiber length and content, the mechanical properties of fibers reinforced concrete increase with the increase of fiber length, and the comprehensive mechanical properties of fine-grained concrete materials are the best when the AR-glass fiber content is about 5%. The flexural performance tests of BTRC sheets show that the strength and the deformation capacity of sheets increase with the increase of the number of fiber textile layers. The short AR-glass fibers can also effectively improve the strength and deformation capacity of BTRC sheets, and the cracking load and ultimate displacement can be increased by up to 1.1 times and 10.1 times of the sheet without short fibers, respectively. For the multi-fiber compound reinforced concrete sheets, the fiber textile can provide tension in the desired direction, and the short AR-glass fibers can improve the cracking resistance and toughness of sheets.